Physical exercise as a potential adjuvant therapy: effects on inflammation and nutrition in colorectal cancer patients—a systematic review and meta-analysis - Zhang, Hui; Zhang, Ying; Luo, Feifei; Wen, Yixin; Ni, Jiang; Wang, Jing (Frontiers in Nutrition, 2025)
IntroductionThis meta-analysis aimed to reveal the effects of exercise training on markers of inflammation and indicators of nutrition in colorectal cancer patients.MethodsWe systematically searched PubMed, Embase, Cochrane, and Web of Knowledge for randomized controlled trials (published between 1 January 1945 and 17 June 2024). Our main outcomes were nutritional status and markers of inflammation analyzed using a random-effects model.ResultsOf the 3,081 identified studies, 15 were eligible and were included in our analysis (N = 996 participants). Compared with the usual care, physical exercise reduced C-reactive protein by a mean of −0.33 mg/dL (95% CI −0.62 to −0.04) in colorectal cancer patients. Similarly, body fat decreased by a mean of −1.36% (95% CI −2.52 to −0.99) after physical exercise. However, interleukin-6, tumor necrosis factor-alpha, and waist circumference were not different between patients who received physical exercise and those who received usual care. Subgroup analyses revealed that exercise duration ≤12 weeks was effective in decreasing body mass index of −0.59 kg/m2 (95% CI −1.15 to −0.02) and body weight of −3.12 kg (95% CI -4.66 to −1.58). In addition, body mass index (p = 0.005) and body weight (p = 0.03) were decreased in patients who combined aerobic exercise and resistance exercise.ConclusionOverall, these findings suggest that physical exercise may improve inflammation status and enhance weight loss in CRC patients.Systematic review registrationNumber CRD 42024536976.